1991
DOI: 10.1016/s0010-9452(13)80130-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in Comprehension of Relative Clauses by Parkinsonian Patients

Abstract: Twenty patients with Parkinson disease (PD) and twenty normal control subjects (NC) matched on age, sex, education and socio-economic status (SES) were tested for comprehension of four types of relative clauses with complex thematic roles (syntax) and no semantic and pragmatic constraints (reversible) in a sentence-picture matching task. The results show a clear language impairment for PD patients compared to NC. Additional evidence from testing school children in grade 1 (G1) and grade 6 (G6) indicates that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 25 publications
5
25
1
Order By: Relevance
“…Paralleling previous work in our laboratory and elsewhere (Cohen et al, 1994;Geyer & Grossman, 1994;Grossman et al, 1991Grossman et al, , 1992Kemmerer, 1999;Lieberman et al, 1990Lieberman et al, , 1992Natsopoulos et al, 1991Natsopoulos et al, , 1993Ullman et al, 1997), we found that the sentence comprehension impairment in PD when measured with a traditional procedure is most evident for grammatically complex sentences. PD patients thus have relatively greater difficulty with sentences containing object-gap subordinate clauses than subject-gap subordinate clauses, particularly when it is the subordinate clause that is being probed.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Paralleling previous work in our laboratory and elsewhere (Cohen et al, 1994;Geyer & Grossman, 1994;Grossman et al, 1991Grossman et al, , 1992Kemmerer, 1999;Lieberman et al, 1990Lieberman et al, , 1992Natsopoulos et al, 1991Natsopoulos et al, , 1993Ullman et al, 1997), we found that the sentence comprehension impairment in PD when measured with a traditional procedure is most evident for grammatically complex sentences. PD patients thus have relatively greater difficulty with sentences containing object-gap subordinate clauses than subject-gap subordinate clauses, particularly when it is the subordinate clause that is being probed.…”
Section: Discussionsupporting
confidence: 89%
“…Sentences with object-gap subordinate clauses have a noncanonical word order where comprehension appears to benefit from executive resources such as inhibition, working memory, information processing speed, and planning. Patients with PD have considerable difficulty understanding object-gap sentences (Grossman et al, 1991(Grossman et al, , 1992Lieberman et al, 1990Lieberman et al, , 1992Natsopoulos et al, 1991Natsopoulos et al, , 1993. We have also shown that PD patients are impaired in their comprehension of other, noncanonical sentence structures (Geyer & Grossman, 1994).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Lieberman et al (1990) attributed the sentence comprehension errors in PD to "some deterioration of the patient's ability to make use of the syntactic 'rules' involved in English" (1990, p. 364). Similarly, researchers have attributed the sentence comprehension deficit to an impairment of some aspects of grammatical processing as such (Cohen et al, 1994;Natsopoulos et al, 1991Natsopoulos et al, , 1993. However, according to Lieberman et al (1990), the cognitive impairments and syntactic comprehension deficits in PD have a common physiological basis; they are both caused by disruption of the cortico-striato-cortical circuits.…”
Section: Comprehension Of Non-canonical Sentencesmentioning
confidence: 99%